Does variation in composition affect dynamics when approaching the eutectic composition? - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Chemical Physics, 2023)
Deep eutectic solvent is a mixture of two or more components, mixed in a certain molar ratio, such that the mixture melts at a temperature lower than individual substances. In this work, we have used a combination of ultrafast vibrational spectroscopy and molecular dynamics simulations to investigate the microscopic structure and dynamics of a deep eutectic solvent (1:2 choline chloride: ethylene glycol) at and around the eutectic composition. In particular, we have compared the spectral diffusion and orientational relaxation dynamics of these systems with varying compositions. Our results show that although the time-averaged solvent structures around a dissolved solute are comparable across compositions, both the solvent fluctuations and solute reorientation dynamics show distinct differences. We show that these subtle changes in solute and solvent dynamics with changing compositions arise from the variations in the fluctuations of the different intercomponent hydrogen bonds.

Solvation structure and dynamics of a small ion in an organic electrolyte - Kore, Shivshankar; Sahoo, Rudhi Ranjan; Santra, Binit; Sarkar, Archishman; Chowdhury, Tubai; Deshmukh, Samadhan H.; Hazarika, Sulagna; Chatterjee, Srijan; Bagchi, Sayan (Journal of Photochemistry and Photobiology A-Chemistry, 2023)
Organic carbonates are commonly used as electrolytes in commercial lithium-ion batteries. A detailed interpretation of the solvation structure and dynamics of the electrolyte around ions is necessary to understand the charge/discharge process in batteries. This work combines infrared absorption spectroscopy with quantum chemical calculations and molecular dynamics simulations to decipher the solvation structure of propylene carbonate, a cyclic carbonate, around the dissolved thiocyanate ion. Two dimensional infrared spectroscopy and polarization-selective pump probe spectroscopies have been utilized to extract the timescales of solvent fluctuation and the solute reorientational dynamics. The similarity in the slow timescales for the solute and the solvent dynamics signifies that similar processes control both dynamics.

Probing surface interactions in CdSe quantum dots with thiocyanate ligands - Deshmukh, Samadhan H.; Yadav, Sushma; Chowdhury, Tubai; Pathania, Akhil; Sapra, Sameer; Bagchi, Sayan (NANOSCALE, 2024)
Keywords: COLLOIDAL NANOCRYSTALS; STRUCTURAL DYNAMICS; Thin-films

Solvation dynamics and microheterogeneity in deep eutectic solvents - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Physical Chemistry B, 2024)
Deep eutectic solvents have attracted considerable attention due to their unique properties and their potential to replace conventional solvents in diverse applications, such as catalysis, energy storage, and green chemistry. However, despite their broad use, the microscopic mechanisms governing solvation dynamics and the role of hydrogen bonding in deep eutectic solvents remain insufficiently understood. In this article, we present our contributions toward unravelling the micro heterogeneity within deep eutectic solvents by combining vibrational Stark spectroscopy and two-dimensional infrared spectroscopy with molecular dynamics simulations. Our findings demonstrate how the composition, constituents, and addition of water significantly influence the heterogeneous hydrogen bonding network and solvent dynamics within these systems. These insights provide valuable guidance for the design of next-generation solvents tailored to specific applications. By integrating experimental and computational approaches, this work sheds light on the intricate relationship between solvation dynamics and nanostructure in deep eutectic solvents, ultimately paving the way for innovative advances in solvent design.

Viscosity effects on the dynamics of diols and diol-based deep eutectic solvents - Chatterjee, Srijan; Deshmukh, Samadhan H.; Chowdhury, Tubai; Bagchi, Sayan (Photochemistry and Photobiology, 2024)
Diols, characterized by the presence of two hydroxyl groups, form extended hydrogen-bonded networks. Increasing hydrocarbon chain length is known to elevate the viscosity of diols. Given the established influence of viscosity on solvent dynamics, it becomes imperative to comprehend the impact of viscosity on the fluctuation dynamics within diols and establish connections with hydrogen bond formation and breaking dynamics. In this study, we employ two-dimensional infrared spectroscopy to investigate the viscosity dependence of the structural evolution dynamics in three diols with varying chain lengths. Complementing our experimental approach, molecular dynamics simulations are conducted to extract hydrogen bond lifetimes. Our findings reveal a linear correlation between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. Notably, the selected diols exhibit the capability to form deep eutectic solvents upon mixing with choline chloride at specific molar ratios. In contrast to molecular solvents like diols, deep eutectic solvents are characterized by the formation of heterogeneous nanodomains, comprising various intercomponent hydrogen-bonded networks. Interestingly, our observations indicate that while the fluctuation dynamics decelerate with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is not linear, in contrast to the observed linearity in diols. This nuanced understanding contributes to the broader comprehension of the interplay between viscosity and dynamics in both molecular and deep eutectic solvents. We investigate the impact of viscosity on structural evolution dynamics in diols with varying chain lengths. Employing two-dimensional infrared spectroscopy and molecular dynamics simulations, we explore the relationship between bulk viscosity, solvent fluctuation timescales, and hydrogen bond lifetimes. We report a linear correlation in diols between viscosity, fluctuation timescales, and hydrogen bond lifetimes. Diols also form deep eutectic solvents, characterized by heterogeneous nanodomains. While fluctuation dynamics slow down with increasing bulk viscosity in diol-based deep eutectic solvents, the relationship between viscosity and dynamics is nonlinear, contrasting with diols' linearity. This understanding enhances comprehension of viscosity-dynamics interplay in molecular and deep eutectic solvents.image
Keywords: Dynamics; Hydrogen bond; solvent; spectroscopy; viscosity

Probing solvent fluctuations in deep eutectic solvents: Influence of probe charge and nano-domain localization - Chowdhury, Tubai; Pathania, Akhil; Ravindranathan, Sapna; Bagchi, Sayan (Journal of Chemical Physics, 2025)
Deep eutectic solvents (DESs) segregate into hydrogen bond acceptor or hydrogen bond donor (HBD) rich nano-domains, leading to molecular heterogeneity. Understanding how this heterogeneity affects the DES structure and dynamics is essential. In this study, we used two-dimensional nuclear magnetic resonance (2D NMR) and two dimensional infrared (2D IR) spectroscopies, combined with molecular dynamics (MD) simulations, to investigate solvation structure and dynamics in two choline chloride-based DESs with different HBDs-levulinic acid and glycolic acid. We introduced two thiocyanate vibrational probes, methyl thiocyanate (CH3SCN, neutral) and ammonium thiocyanate (NH4SCN, anionic), which selectively localize in specific nano-domains. 2D NMR provided insights into solvent structure and probe location, while 2D IR captured solvation dynamics. Our results show that these small probes do not alter the solvent structure, regardless of charge. However, solvation dynamics depend on long-range electrostatic ordering in the DES and the local shielding effects of the nano-domain where the probe resides. MD simulations complement experimental findings, providing a molecular-level understanding of solvation in DESs.